Social and legal status of teachers of secondary schools in Belarus in the second half of XIX – early XX century - Astroha, Valiantsina M. (Journal of the Belarusian State University. History, 2019)
By the middle of the XIX century the government policy in the sphere of public education of Russia did not meet the urgent needs of socio-economic and cultural development of the country. School reform in 1864 gave impetus to the modernization of the existing education system, putting on the agenda the problem of providing educational institutions of all types of qualified teaching staff. The social status of teachers in secondary schools was determined by a broad legal framework, which established the range of rights and duties of the «student» (laws, decrees, orders, circulars, statutes, instructions, etc.), as well as the level of material income – the degree of security of life and wealth, an indicator of the prestige and position in society of representatives of this intelligent profession.
Keywords: teacher intelligentsia; educational district; secondary schools; gymnasiums; real schools; social and legal status; educational process